Obtenção e caracterização de nanopartículas lipídicas sólidas como sistema de transporte para ibuprofeno - Depaoli, Ana Cláudia da Cunha [UNESP] (2014)
The ibuprofen (IBU), a non-steroidal anti-inflammatory (NSAID), has analgesic, antipyretic and anti-inflammatory action. It is clinically recommended for symptomatic relief of headache, myalgia and of chronic degenerative diseases such as osteoarthritis and rheumatoid arthritis. It is well known in the literature that the IBU has a short half-life, and is a poorly water soluble drug. In addition, the treatment with IBU can result in high levels of gastrointestinal toxicity. To work around these limitations, an alternative would be the encapsulation of IBU in delivery systems, such as solid lipid nanoparticles (SLN). Currently SLN have been developed as carriers for lipophilic drugs, in order to obtain a controlled release and targeted drug with reduced side effects, thus having an increasing efficacy of the treatment. The objective of this work was obtaining and characterization of SLN containing IBU. The SLN were prepared by sonication technique, glyceryl monostearate (GMS), hydrogenated soy phosphatidylcholine (FSH) and poloxamer 188 (P-188) were used as excipients for the development of formulation. The SLN without and with drug showed mean particle size in the nanometer range, the size was greater as increased the concentration of drug in the system. Morphological characterization showed irregular shape of the SLN and when increased as the concentration of drug in the system approached the spherical shape. The formulations showed high encapsulation efficiency. Stability study showed that the SLN containing IBU were stable over the period of 60 days. The differential scanning calorimetry (DSC) showed that the drug is molecularly dispersed in the lipid matrix and the matrix is in solid state. The thermogravimetric analyzer (TG) showed that the IBU incorporated in SLN have a greater thermal stability compared to pure drug. The release of drug was controlled for all concentrations and showed an in vitro release profile according to ...